PERSEPSI PEMUSTAKA TERHADAP KOLEKSI DIGITAL DI PERPUSTAKAAN IAIN KEDIRI - Aulawi, M Basith; Mauludin, M Soleh (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This study aims to analyze the perception of users towards digital collections at the IAIN Kediri Library. Along with the development of technology, modern libraries increasingly rely on digital collections to meet the information needs of their users. This study uses a qualitative method with a survey approach. Data were collected through questionnaires distributed to a sample of users consisting of IAIN Kediri students. The results of the study showed that most users had a positive perception of the digital collections of the IAIN Kediri Library. They considered that digital collections were easily accessible, relevant, and useful to support academic and research activities. However, some users also identified several obstacles such as limited internet access and lack of socialization related to digital collections. This study concludes that the IAIN Kediri Library has succeeded in providing quality and relevant digital collections for users. However, ongoing efforts are needed to overcome existing obstacles and improve the optimal use of digital collections Keywords: Perception, Librarian, Digital Collection